Comportamento operacional de elementos sulcadores de fertilizante em função da distância dos mesmos para o mecanismo de corte - Francetto, Tiago Rodrigo (2017)
The objective was to determine the effect of longitudinal distance between coulters and furrow openers about the operational performance of these associations working in different forward speeds, with regard to the energy requeriment and the amount of furrow, with the purpose of identifying the integration mechanism/regulation that presents the lowest energy consumption without compromising the quality of the furrow. This was carried out in an agricultural area located in the municipality of Santa Maria (Rio Grande do Sul), belonging to Universidade Federal de Santa Maria. The soil of the experimental area was classified as Ultisol and sandy. The experiment was composed of 24 combinations of treatments, in a factorial scheme of 2x3x4. These were composed by the interaction of the factors groove opening mechanisms (hoe furrow opener and mismatched double discs), longitudinal distance from center to center of coulter and furrowers (0,50,1,0 e 1,50 m) and forward speeds (1,11, 1,67, 2,22 e 2,78 m s-1). The variables responses of the performance of the mechanisms associations were obtained directly or indirectly, through the application of different methods by different tools. After the acquisition of the data, they were submitted to statistical analysis of variance and verified the significance of the factors through the F test. In addition, a mathematical analysis of the instantaneous rate of change, with the use of the differential calculus. The furrow, distance and velocity factors had a statistically significant influence on the primary performance variables resulting from instrumentation, except the distance factor on the slipping of the driving wheels. For the variables of soil mobilization, the furrow factor provided a significant change in all, while the distance factor significantly modified only the raised area and the maximum furrow depth. Already the velocity, interfered significantly in the latter and in the area of mobilized soil. In addition, in the secondary variables, the modification of the furrow and speed factors did not provide significant change only in the variable soil swelling, while the distance did not change the specific fuel consumption. The traction, the hourly consumption and the skating were higher for the configurations that employ the hoe furrow opener, present greater distance and work at higher speeds. The distance did not modify the mobilized area, the width and the depth of the furrow, and the reduction of this reduced the elevated area. The use of lower speeds and distances provides greater efficiency in the use of traction per unit of depth and of soil mobilized for both furrowers.